Why I am a democrat - Sorensen, Theodore C. 1928-2010 (Holt, 1996)
For those Americans who have questioned or forgotten the aims and strengths of the Democratic Party, a well-known Democrat from the Kennedy era has written a thoughtful reminder. Ted Sorensen was the principal counsel, policy adviser, and speechwriter for President Kennedy and has experienced more than four decades of political activity. Here he articulates the fundamental reasons and principles behind proclaiming oneself a Democrat. In Why I Am a Democrat, Sorensen defines himself in terms of the major themes on which Democrats and Republicans divide - their differing approaches to government and the free market, to national and individual distress and discrimination, to privacy and public service. Outlining his own vision and ruminating about the roots of that vision, he provides a skeleton key for the Democratic impulse